Epidemiological Trends of Fungal Pulmonary Infections Post-COVID-19 - Ahmad, Muhammad Ayaz; Kumari, Pirya; Sikandar, Muhammad Rumman; Baig, Junaid Islam (Indus Journal of Bioscience Research, 2025)
Background: Fungal infections of the lungs have developed into a significant concern after COVID-19, especially for patients with predisposing risks like diabetes and previous use of corticosteroids. The combination of clinical signs with viral pneumonia frequently results in missing the diagnosis and negative consequences. To assess the epidemiological characteristics, risk factors, clinical presentation, and outcomes of patients who developed fungal pulmonary infections after recovering from COVID-19. Methods: This was a cross-sectional study conducted from July 2023 to July 2024 at the department of Medicine, DHQ hospital, Lodhran and it included 82 post-COVID patients with pulmonary fungal infections. Demographic information, comorbidities, treatment history of COVID-19, classification of the fungal infection, and the outcomes of the disease were analyzed in SPSS version 25. Statistical relations were tested using the chi-square test and Fisher’s exact test. Results: Most of the patients were males (65.9%) and above 40 years. The diabetes mellitus incidence (52.4%) and history of corticosteroid use (68.3%) were markedly linked with fungal infection. Most frequent pathogens were aspergillus (45.1%) and mucormycosis (26.8%). The most prevalent symptoms were cough, fever, and dyspnea. The recovery rate was at 74.4% and mortality rate was at 14.6%. Conclusion: Fungal pulmonary infections post-COVID-19 are linked with severe disease and high morbidity, especially in patients with diabetes or who received immunosuppressive therapy. Early recognition and targeted treatment are crucial to improve outcomes.